Gender Wise Comparison Of Sitting Time And Sleep Pattern Of Obese Individuals From A Cross Sectional Study Conducted At South Kerala, India (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Obesity is a global pandemic and south Asians are especially victims of developing unhealthy body composition. Sleep deprivation and prolonged sitting are two contributors for developing fat deposition and metabolic syndrome. The present study was conducted with an objective to analyse the between gender difference in sitting time and sleep quality of respondents with overweight and obesity. Methodology: This was a cross sectional survey conducted as part of research on obesity from 2015-2018 at Thiruvananthapuram, Kerala. The criteria for inclusion in the study were overweight and obese adults aged 18-65 years from both genders. Respondents who were underweight and those suffering from diseases requiring strict food restrictions were excluded from the study. A structured questionnaire was used to collect data on demographic pattern, anthropometric profile, sitting time in hours and sleep pattern. Results: The data of about 500 respondents were collected for the study including 217 male and 283 female respondents. Both genders shared similar age distribution (46.34±11.37 years in males vs 46.07±11.37 years in females) and demographic profile. Anthropometric profile exhibited an unhealthy body fat percentage in both the genders. Males and females had moderate sitting habits and males on average were seated more by 1.85 hours than females. The sleep duration was satisfactory for both the genders but the sleep quality was poor. Comparatively the sleep quality of males were poorer than females. Conclusion: The body fat percentage was unhealthy in the respondents with overweight and obesity and the detrimental influence of sitting time and sleep quality was more vivid in the case of males.